Empowering and Influencing Factors of Intellectual and Spiritual Capital in Improving Organizational Performance at Tourism Institutions - Ariyanto, Agus; Adam, Muhammad; Musnadi, Said; Djalil, Muslim A (Journal of Ecohumanism, 2024)
This research aims to measure factors that influence intellectual and spiritual capital in increasing organizational performance at tourism institutions in Banda Aceh City through the variable organization. The methodology used is quantitative. Data was collected from respondents using a structured questionnaire with a Likert scale. Seventy-five questionnaires were distributed in all to the Banda Aceh City Tourism Institution. Sample selection utilized a disproportionate technique of stratified random sampling. The research data underwent descriptive, and structural equation modeling analysis using SPSS and SEM AMOS software. The analysis that was produced was: Research has demonstrated that intellectual capital has a substantial and favorable impact on the functioning of organizations, that is 0.000 < 0.05 as the significant value; spiritual capital has a -0.070 direct effect on organizational performance; the coefficient of the indirect effect is 0.273, the mediation process has a substantial impact, and the effect of mediation has been proved to be significant, the coefficient for the indirect effect is 0.458, at the lower level for intellectual capital boot of 0.227, and the upper level for intellectual capital of 0.676, with a 95% confidence interval.